วาทกรรม "ชาวบ้าน" กับการจำกัดตนเองในการมีส่วนร่วมทางการเมือง - จารุวรรณ แก้วมะโน (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This study sought to explain the supposedly low level and ineffectiveness of political participation of Chaoban (ordinary people) in Thailand. Deeming political cultural explanations to be inadequate, it made use of Michel Foucault s concept of the Subject and Power together with the concept of three faces of power in doing so. The hypothesis was that the state constructed the meaning of Chaoban in such a way as to have made the Chaoban feel politically inadequate such that they limited their own political participatory roles. Apart from documentary research, field research involving semi-structured interviews was conducted in a rural area in Lampang Province and an urban area in the Bangkok Metropolis. This was order to discover locality differences, if any, in the outcomes of the process of construction of the self on Chaoban s self-perceptions of inadequacy and political participatory behaviour. The finings were that there were correlations between the state s construction of the self in Choaban and their self-perception of inadequacy including their self-limiting political participatory behaviour. However, the correlations did not always obtain. It was not always the case that the Chaoban would perceive their inadequacy nor would limit their own political participation. The behavioural stage depended on other environmental factors which mediated between perception and behaviour. It was found also that the Chaoban exhibited many forms of resistance to state power. This indicated that they were not mere objects of state action but had their own tactics in responding to the state. None the less, this did not mean that the Chaoban did not exhibit self-limiting political behaviour. It was rather that such self-limitation involved a complex process